Inside-out Meniscal Repairs in the Setting of Multiligament Reconstruction in the Knee: Does Meniscal Repair Affect Outcomes and Failure Rates?. Issue 7 (21st July 2017) - Mitchell, Justin J.; Chahla, Jorge; Cinque, Mark; Dean, Chase S.; Matheny, Lauren M.; LaPrade, Robert F.
Objectives: The purpose of this study was to assess outcomes and failure rates of meniscal repair in patients who underwent multiligament reconstruction compared to patients who underwent multiligament reconstruction but lacked meniscal tears. We hypothesized that the outcomes of meniscal repair associated with a concomitant multiligament reconstruction would significantly improve from preoperatively to postoperatively at a minimum of 2 years following the index surgery. Secondarily, we hypothesized that this cohort would demonstrate similar outcomes and failure rates compared to the cohort who did not have meniscal pathology at the time of multiligament reconstruction. Methods: Inclusion criteria for the study included radiographically confirmed skeletally mature patients over 16 years of age who underwent multiligamentous reconstruction of the knee without previous ipsilateral osteotomy, intraarticular infection, or fracture. Patients were included in the experimental group if they underwent inside-out meniscus suture repair with a concurrent multiligament reconstruction. Those included in the control group (multiligament reconstruction without a meniscal tear) underwent multiligament reconstruction, but did not have any type of meniscal surgery. Lysholm, WOMAC, SF-12 PCS and MCS, Tegner Activity scale and patient satisfaction were recorded preoperatively and postoperatively. Failure of the meniscal repair was defined as a re-tear of the meniscus that was confirmed arthroscopically. Results: There were 43 patients (16 females, 27 males) in the meniscal repair group and 62 patients in the control group (25 females, 37 males). Follow-up was obtained in 93% of patients with an average follow-up of 3.0 years (range, 2.0 to 4.7 years). There was a significant improvement between all preoperative and postoperative outcome scores (p<.05) for both groups. The multiligament plus meniscal repair group had significantly lower preoperative Lysholm and Tegner scores (p=0.009, p=0.02, respectively). There were no significant differences between any other outcome score at preoperative status. There was no significant difference in any postoperative outcome score at a minimum two-year follow up between the two groups. Conclusion: Good to excellent patient reported outcomes were reported for both groups with no significant differences in outcomes between cohorts. Additionally, the failure rate for an inside-out meniscal repair with a concomitant multiligament reconstruction was low, regardless of meniscus laterality and tear characteristics. The use of multiple vertical mattress sutures and the biological augmentation resulting from intra-articular cruciate ligament reconstruction tunnel reaming may be partially responsible for the stability of the meniscus repair construct and thereby contribute to the overall improved outcomes and a low failure rate of meniscal repair despite lower preoperative Lysholm and Tegner scores in the meniscal repair group.